(untitled) (Proceedings of the International Conference on Education, 2020)
The challenge of teachers in the era of the industrial revolution 4.0 is inevitable, the teachers must keep abreast of continued technological developments, including in the making of instructional media. Not infrequently they face quite serious problems when making ICT-based instructional media. This paper aims to understand (1) What causes problems in making ICT-based learning media appear; and (2) How these problems can arise. The method used is qualitative with a phenomenological approach. Data collected from results of in-depth interviews and participatory observation. The informants in this study consist of all social studies teachers at Brawijaya Smart School, one of the best junior high schools in Malang, Indonesia. The collected data were analyzed using the stages of Transcription, Horizonalization, and Cluster of Meaning. The study results show that problems in making ICT-based instructional learning media arise due to: (1) Lack of habituation, (2) the age of the teacher (3) no assistance, (4) generation, (5) too many additional assignments from school, and (6) limited of time. The conclusions from this study show that a great wall of problems arises because of internal and external sides. From the internal side is the attitude that is built up in the social studies teacher, while from the external side is the attitude that is built up within the school and government policy. Between these two things (internal and external) there hasn’t been a harmonization that supports each other.